Determinan Pertumbuhan Deposito Mudharabah Pada Bank Umum Syariah Di Indonesia - As’adinnas; Ahdiyat Agus Susila; Cici Widya Prasetyandari (DPPM Universitas Pelita Bangsa, 2025)
This study aims to analyze the impact of profitability, capital adequacy, operational efficiency, and problematic financing on the growth of mudharabah deposits in Islamic banks in Indonesia for the period 2019-2023. The method used in this study is a quantitative method with secondary data obtained from the annual financial reports of Islamic banks. The data analysis technique uses multiple linear regression. The findings suggest that only the variable (ROE) has a significant impact on mudharabah deposits, while the CAR, BOPO and NPF variables do not have a significant impact. The coefficient of determination (adjusted R2) suggest that the four independent variables simultaneously explain 32.6% of the variation in mudharabah deposit growth. This finding shows the importance of profitability in attracting customer interest in mudharabah deposit products, while other factors require further study. The study provides implications for Islamic bank management to focus more on improving profit performance in order to increase fund collection from mudharabah deposit products.